FREQUENCY AND SIGNIFICANCE OF THE DEVELOPMENT OF FEBRILE NEUTROPENIA IN PATIENTS WITH HEMATOLOGICAL MALIGNANCIES TREATED IN THE DAY-CARE UNIT OF A TERTIARY INSTITUTION - Kecman, Natalija; Lemajić, Nikola; Tomić Vujović, Kristina; Arsenović, Isidora; Smiljanić, Mihailo; Sretenović, Aleksandra; Virijević, Marijana; Vuković, Vojin; Suvajdžić-Vuković, Nada; Vidović, Ana; Bila, Jelena; Antić, Darko; et al. (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Chemotherapy-induced neutropenia is often complicated by the development of febrile neutropenia (FN) which is associated with infections, dose reductions/delay of chemotherapy, quality of life deterioration, and increased treatment costs. Aims: The study aims to research the association between risk factors for FN and the significance of applying G-CSF in patients with hematological malignancies. Methods: We evaluated 90 patients with lymphoma, multiple myeloma (MM), and myelodysplastic syndrome (MDS) treated at the Day-care Unit of the University Clinical Center of Serbia (UCCS) Clinic for Hematology, between January and June 2024. Results: The study included 90 patients with the following diagnoses: 70 (77.8%) patients with lymphomas, 12 (13.3%) patients with MM, and 8 (8.9%) patients with MDS, of whom 42.2% (38/90) male and 57.8% (52/90) female. Febrile neutropenia (FN) was observed in 22 (24.4%) patients, while 68 (75.6%) patients did not develop FN. The distribution of FN by lymphoma type was as follows: 57.9% in aggressive lymphomas, 31.6% in indolent lymphomas, and 10.5% in Hodgkin’s lymphoma. FN was associated with a higher incidence of advanced clinical stages of disease, with 70% in stages III and IV. Patients with FN had significantly higher rates of bulky tumor mass (54.5% vs. 25%; p = 0.010), more lines of chemotherapy (p = 0.020), more cycles of chemotherapy (p = 0.027), more immunotherapy cycles (p = 0.025), as well as more infections (59.1% vs. 27.9%; p = 0.008), antibiotic use (95.5% vs. 33.8%; p = 0.004), and G-CSF administration (54.5% vs. 11.8%; p < 0.001), with more G-CSF ampoules used (5.0 vs. 1.0; p < 0.001). Higher CRP levels were also significantly associated with FN (7.2% vs. 3.3%; p = 0.012). Conclusion: Our study has shown that the number of lines of therapy, the number of immunochemotherapy cycles, the clinical stage, the presence of bulky tumor mass, and the aggressiveness of the lymphoma affected FN development.